Disaster education in Turkey: Trends in theses and articles between 2003 and 2020 - Ufuk Sözcü (Journal of Pedagogical Research, 2020)
Many disastrous events have taken place in Turkey, most of which have been of natural origin. When the loss of life and property caused by these disasters is analyzed, the increasein recent years is striking. "Disaster education", given in order to prevent and the negative consequences of such disasters, is of great importance. Within the Turkish educational system, courses in life sciences, social studies and science, and, in particular, in geography provide some scope for disaster education. At university level, disaster education courses may be offered directly or indirectly in departments of primary education, science, social studies and geography, as well as in specific courses on emergency and disaster management. The aim of this study was to evaluate studies of disaster education from kindergarten to university level. To this end, the document review method, one ofthe qualitative research techniques, was used. Two doctoral theses, 27 master's theses and 29 scientific articles published between 2003 and 2020 were evaluated. These studies were foundas a result of an internet search using the keywords 'disaster' and 'disaster education' in the HEB Thesis database. The data obtained were analyzed using the content analysis method. The studies were evaluated according to the subject, method, findings and results of the research. As a result of the research, it was determined that the studies on disaster education have increased in quality and quantity in recent years. It was observed that studies have been carried out on a number of different subjects, from 'information about disasters' to'perceptions of disasters' to 'disaster behaviors', but that experimental studies were few in number. In the light of these results, recommendations are made aboutfuture disaster education.